How does auditory training work? Joined up thinking and listening - Ferguson, Melanie A.; Henshaw, Helen (Thieme Publishing, 2015)
Auditory training aims to compensate for degradation in the auditory signal and is offered as an intervention to help alleviate the most common complaint in people with hearing loss, understanding speech in a background noise. Yet there remain many unanswered questions. This article reviews some of the key pieces of evidence that assess the evidence for whether, and how, auditory training benefits adults with hearing loss. The evidence supports that improvements occur on the trained task; however, transfer of that learning to generalized real-world benefit is much less robust. For more than a decade, there has been an increasing awareness of the role that cognition plays in listening. But more recently in the auditory training literature, there has been an increased focus on assessing how cognitive performance relevant for listening may improve with training. We argue that this is specifically the case for measures that index executive processes, such as monitoring, attention switching, and updating of working memory, all of which are required for successful listening and communication in challenging or adverse listening conditions. We propose combined auditory-cognitive training approaches, where training interventions develop cognition embedded within auditory tasks, which are most likely to offer generalized benefits to the real-world listening abilities of people with hearing loss.